Methodological aspects of forming abilities and skills of physical self-improvement at different stages of realization of educational objectives of the system of physical education of students - Jhuravel' O. O. (Kharkov National Pedagogical University, 2012)
In this article is shown the problem of realization of humanism principles, consciousness and activity in the process of physical education of students of higher educational institutions. Developed a method of obtaining knowledge regarding the benefits of systematic exercise and determined organizational features of the implementation of the appropriate control. The proposed guidelines also provide for the presence of several stages of formation of skills of independent studies of physical culture taking into account the interests and needs of the student contingent. On the first course is offered to acquire knowledge and ensuring the skills of independent planning of individual classes. On the second year of education provides for the implementation of the personal creative potential of students in the process independent of physical exercises under the guidance of the teacher. It is suggested to examine personality of student as open dynamic system with many intercommunications and structural connections, which is apt at self-perfection.